L’artificieuse alternative de Ford Madox Ford dans The Good Soldier - Catherine Pesso-Miquel (Sillages Critiques)
In The Good Soldier Ford Madox Ford used artifice in order both to construct and deconstruct, simultaneously. This article begins by analysing the various devices used by modernist and postmodernist novelists to break the frame of narrative illusion (devices often based on an either/or opposition), before showing that Ford boldly preferred the conjunction and, piling up aporetic contradictions and incompatibilities that operate at the level of plot, grammar, time scheme, and characterisation. Thus the novel brilliantly creates the illusion that there is an elaborate, rich story to be understood and interpreted while at the same time preventing any satisfactory piecing together, by the reader, of all the details and fragments of this discontinuous tale. The Good Soldier is not a modernist tale protesting that it is only a metafictional discourse, it is a flat, brilliant metafictional surface creating the illusion that this “saddest story” does have a depth.